Biomechanical analysis of intact versus ruptured Poly Implant Prothèse breast implants. Issue 4 (6th August 2019) - Ramião, N. G.; Martins, P. S.; Barroso, M. L.; Santos, D. C.; Fernandes, A. A.
Abstract : Despite there being many studies that have evaluated breast implant rupture, there is no consensus about causes and incidence. Most studies lack a multifactorial analysis of what causes breast implants to rupture. To fill this gap, an experimental protocol was developed to compare ruptured and intact Poly Implant Prothèse (PIP) breast implants from the same woman. These conditions guarantee that the physical/biological variables are the same for each pair of ruptured and intact implants. A total of 1008 samples from 22 PIP explants (11 intact and 11 ruptured) and three control PIP implants were analysed. The mechanical properties (tensile strength) of the ruptured and intact implants were compared according to brand, lot, implantation time and demographic conditions. In general, statistically significant differences were found between the intact and ruptured PIP implants. Ruptured implants were thinner (0.73 ± 0.10 mm versus 0.91 ± 0.11 mm) and weaker (7.42 ± 2.65 MPa versus 9.59 ± 2.37 MPa) than intact implants. Intact and ruptured implants have shown distinct mechanical behaviours and variations in thickness. Our understanding is that these differences may be associated with the typical manufacturing process of breast implant shells. These results stress the importance of thorough control of the shell thickness. Given its relevance, shell thickness should be used as a quality control measure for homologation purposes. Thus, the homogeneity of the shell should be considered as a relevant parameter during the manufacturing process. This will translate into an improved quality of life for patients and will potentiate safer and longer lasting products.